Exploring The Experiments of Mass Distributions of Bed Nets in The Community to Prevent Malaria in Kisantu Health Zone, Democratic Republic of Congo: A Qualitative Study - Ilombe, Gillon; Miaka, Nicole Muela; Lulebo, Aimee; Maketa, Vivi; Kalonji, Yanneeck; Baloji, Sylvain; Kahunu, Mesia; Mpanya, Alain; Lutumba, Pascal (British Journal of Healthcare and Medical Research, 2023)
Despite its discovery more than a century, malaria remains a of public health problem. One of the pillars in the strategy to fighting it is the use of the mosquito net, which remains the only significant tool of prevention. This study is to evaluate the knowledge, perception and experiments of the mass campaign distribution of the mosquito nets in the community one year after the distribution. A qualitative study, centered on households, was carried out in the community of Kisantu Health Zone (KHZ) in the end of clinical trial in 2019. The semi-structured interviews with community leaders and individual focus groups with women having at least one child, were selected in six villages of the of KHZ. Among the respondents, the all had a good level of knowledge of mosquito nets, namely the proper definition of a mosquito net, the correct mode of installation in a sleeping space and that the occurrence of such holes in a mosquito net could be repaired but that was grounds for its inefficiency. The minority either cleaned the mosquito net with powdered laundry soap, and spread out to dry under the sun. The undesirable events related to the use of long-lasting insecticide-treated nets (LLINs) as well as occurrence of holes was quoted by a minority of the respondents as grounds of the weak use of LLINs in households. After one year of distribution, majority possession and the minority gave up use because of attrition or an adverse effect allotted to the use of LLINs.